Hubungan Dukungan Keluarga ODHA dengan Kepatuhan Minum Obat Antiretroviral di Klinik VCT Sobat Kupang - Dahoklory, Beatrice Mardiana; Romeo, Petrus; Takaeb, Afrona E. L. (Faculty of Public Health, Nusa Cendana University, 2019)
Family support to people with HIV and AIDS (PLWHA) plays an important role in improvement of PLWHA to take antiretroviral drugs (ARV) obediently. Commonly, PLWHA is an introvert person mainly about his/her health condition, so if the family have less knowledge and support during the treatment process, she/he would not be obedient to take ARV drugs and the therapeutic effect could not work optimally. This study aimed to determine the relationship between family support with compliance taking ARV drugs on PLWHA in-Clinic VCT Sobat RSUD Dr. W. Z. Johannes Kupang. The type of this research was analytical survey with a crosssectional study design. The number of respondents were 44 people which obtained by using accidental sampling technique. The data was collacted by using questionnaire and was analysed by using Chi-square test. The results showed that there was a relationship between support for assessment (p = 0,003), instrumental support (p = 0,001), emotional support (p = 0,028), and no relation of informational support (p = 0,336) with compliance taking ARV drugs on PLWHA. Thus, it is expected that family should continue to support the PLWHA to provide accurate information about ARV treatment and to remind PLWHA to take ARV drugs regularly.